2004
DOI: 10.3354/cr025217
|View full text |Cite
|
Sign up to set email alerts
|

Baltic Sea ice seasons in the twentieth century

Abstract: We examine the evolution of ice seasons in the Baltic Sea during the 20th century based on a set of 37 time series from the coastal observation stations. The statistical question of combining data from sites with different ice probabilities is solved by using fractiles of the distributions. These 100 yr long time series, including date of freezing, ice break-up, number of days with ice, and maximum annual ice thickness, provide evidence of a general trend toward easier ice conditions; the largest change is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 16 publications
5
35
0
Order By: Relevance
“…This is visible in, e.g., seabed erosion (unpublished data). During the last decades, sea ice is observed at Utö every few years (Jevrejeva et al, 2004) while summertime cyanobacterial algae blooms are observed almost annually, in July or August (e.g., Kahru et al, 1994;Seppälä et al, 2007).…”
Section: Measurement Site and General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is visible in, e.g., seabed erosion (unpublished data). During the last decades, sea ice is observed at Utö every few years (Jevrejeva et al, 2004) while summertime cyanobacterial algae blooms are observed almost annually, in July or August (e.g., Kahru et al, 1994;Seppälä et al, 2007).…”
Section: Measurement Site and General Characteristicsmentioning
confidence: 99%
“…Recently, Utö station was selected as one of the World Meteorological Organization (WMO) long-term observing stations in the recognition of its irreplaceable cultural and scientific heritage (World Meteorological Organization, 2017). However, despite observations having started already in 1881, a limited number of meteorological studies (e.g., Riihelä et al, 2015;Laapas and Venäläinen, 2017) and only few studies focusing on sea ice and hydrography (Ahlnäs, 1961;Haapala and Alenius, 1994;Haapala and Leppäranta, 1997;Jevrejeva et al, 2004) have been published. One reason for this is that a significant part of the observation data has not been digitized or quality assured until the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring activity in the Baltic Sea is limited to the landfast ice regions, where the sea ice could be thinner than in the drift ice regions. According to Jevrejeva et al (2004), the ice thickness time series around the Baltic Sea coast does not show any consistent trend: both decreasing and increasing trends were reported. A recent study by Ronkainen (2013) supported these conclusions.…”
Section: Ice Thicknessmentioning
confidence: 99%
“…Ice Duration Jevrejeva et al (2004) has compiled the most extensive analysis of ice season changes in the Baltic Sea to date, using time series at 37 coastal stations from the Bothnian Bay to the Arkona Basin. In general, observations showed a tendency towards milder ice conditions.…”
Section: Ice Extentmentioning
confidence: 99%
See 1 more Smart Citation